Generating Social Capital
VII, 256 p.
Keywords: Social capital - networks of civic engagements, norms of reciprocity, and attitudes of trust - is widely seen as playing a key role for the health of democracy. While many authors have examined the consequences of social capital, there is a pressing need to explore its sources. This collection brings together leading American and European scholars in the first comparative analysis of how social trust and other civic attitudes are generated. The contributors to this volume examine the generation of social capital from two directions: society-based approaches that emphasize voluntary associations, and institutional approaches that emphasize policy.